A journey in translation : Anne Hébert's poetry in English - Bessette, Lee Skallerup, 1977- (Canadian literature collection., 2016)
"Anne Hébert is one of Quebec's most widely-read and celebrated authors and is one of Quebec's most-translated authors into English. Anne Hébert is a rarity in Canadian Literature, as there has been a multiplicity of translations of her poetry. She is also one of the most anthologized poets from French Canada. Moreover, the process of translating Hébert's poetry has also left in its wake a number of archival and other paratextual resources that chronicle the individual acts of translation and their reception. All of these materials are invaluable in understanding the systems in place that influence the mediated process that is translation, as well as canon formation. This dissertation 'deals with those in the middle, ' those who are responsible for Anne Hébert's image as a poet in English and her insertion into various canons. It is a narrative history on the evolution of her image as a poet in English."--